Analysis of The Influence of Leadership Attitude of Health Center Personnel with Protection of Health Education on Communities in The Klender III Area - Fiandie, Ursula Jacqueline; Mawene, Marcha Jeanne; Putri, Nabila Aulia Adek; Maharani, Nabilah Liztha; Khairunnisa, Nasywa; Salma, Athifa Huurun; Dalida, Naumy Syauqina; Arvrian, Addyne Aulyfah; Yayi, Dwi Desi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Healthcare worker is a job that requires anyone in this profession to have a great responsibility, especially towards their patients in the healthcare institution. This research was guided by our concern regarding the increasing low level of public satisfaction with health services in Indonesia several years ago. This issue is connected with the leadership possessed by healthcare workers along with the responses of the head of healthcare institution, so the primary aim of our research is to correlate the influence and impact of leadership with the level of public satisfaction with the service and protection of health workers. In this research, healthcare workers that acted as our object of research are healthcare workers of Puskesmas Pembantu of Klender III District